The relationship between parenting style and bystander’s promotion of cyberbullying among college students: the mediating effect of neuroticism and moral disengagement - Wang, Bing; Liu, Chang (Frontiers in Psychology, 2025)
To explore the relationship between parenting style and bystander’s promotion of cyberbullying among Chinese college students, as well as the mediating effect of neuroticism and moral disengagement. A total of 495 college students were selected as participants in this study. The short form Egna Minnen av. Barndoms Uppfostran for Chinese, the revised Eysenck Personality Questionnaire-Short Scale for Chinese, Moral Disengagement Scale and Cyberbullying Bystanders Behaviors Questionnaire were used to conduct the test. The results showed that: (1) rejection was positively correlated with neuroticism, moral disengagement and bystander’s promotion of cyberbullying; Emotional warmth was negatively correlated with neuroticism, moral disengagement and bystander’s promotion of cyberbullying. Neuroticism and moral disengagement were positively correlated with bystander’s promotion of cyberbullying. (2) The mediating effect analysis showed that the direct effect of parenting style (rejection and emotional warmth) on the bystander’s promotion of cyberbullying was significant. In the relationship between parenting style (rejection and emotional warmth) and bystander’s promotion of cyberbullying, the mediating effect of neuroticism and moral disengagement and the chain mediating effect of neuroticism and moral disengagement were significant.